The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/adma.202000928
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Probing of the Tribovoltaic Effect at the Sliding Interface of Two Semiconductors

Abstract: can be generated by the contact or sliding of a P-type semiconductor against an N-type semiconductor [7][8][9] (or semiconductor against metal [10][11][12] ), and a novel electric generator was proposed. [7] This new type of electric generator is gaining attention for that a direct current can be generated without a rectifier module. [8][9][10][11] However, the mechanism of the current generation in the CE involving semiconductors is still under debate.For the contact between a P-type semiconductor and an N-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 36 publications
2
78
0
3
Order By: Relevance
“…Zheng et al demonstrated a DC output based on tribovoltaic effect by using a diamond (n-type) coated AFM tip to rub on the Si wafers (Figure 7d). [113] The current will flow the p-type sample to the n-type tip through external circuit, which is consistent with the proposed tribovoltaic effect. The current mapping for p-type and n-type Si wafers with different doping concentrations and corresponding cross-sectional line analysis are shown in Figure 7e.…”
Section: Development Of Semiconductor-based Dc-tengs In Tip Contactsupporting
confidence: 83%
See 4 more Smart Citations
“…Zheng et al demonstrated a DC output based on tribovoltaic effect by using a diamond (n-type) coated AFM tip to rub on the Si wafers (Figure 7d). [113] The current will flow the p-type sample to the n-type tip through external circuit, which is consistent with the proposed tribovoltaic effect. The current mapping for p-type and n-type Si wafers with different doping concentrations and corresponding cross-sectional line analysis are shown in Figure 7e.…”
Section: Development Of Semiconductor-based Dc-tengs In Tip Contactsupporting
confidence: 83%
“…Obviously, the tribo-tunneling output signal polarity is determined by the surface potential difference between frictional materials. Moreover, the tribovoltaic effect in nanoscale range (Figure 7g) and the influence of the surface characteristics of the semiconductors is further studied by Zheng et al [113] A higher surface states density of the semiconductor materials can be obtained via the inductively coupled plasma reactive ion etching (ICP-RIE) treatment. Figure 8g,h compares the volt-ampere characteristic of the p-n junction before and after treatment.…”
Section: Working Mechanisms Of Semiconductor-based Dc-tengs In Tip Comentioning
confidence: 99%
See 3 more Smart Citations